2016
DOI: 10.1159/000448136
|View full text |Cite
|
Sign up to set email alerts
|

Voice Range Profiles of Singing Students: The Effects of Training Duration and Institution

Abstract: Objective: The aim of the study was to assess differences in voice parameters measured by the physiological voice range profile (VRP) in groups of vocally healthy subjects differentiated by the duration of vocal training and the training institution. Patients and Methods: Six basic frequency- and intensity-related VRP parameters and the frequency dip of the register transition zone were determined from VRP recordings of 162 females studying in individual singing lessons (1st-5th level) in Dutch, Belgian, Engli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
4
3
0
Order By: Relevance
“…These findings resemble the data of nonsinging children described by Siupsinskiene and Lycke [30]. The contrast of frequencies between the sexes is easily visible when comparing 16-year-old males with a minimum frequency of 81.9 Hz (GЬ 2 ) and females with 175.0 Hz (F 3 ), the latter resembling the values found by Lycke and Siupsinskiene [34] for female nonsingers. A similar descent is shown with the variable maximum frequency as depicted above.…”
Section: Discussionsupporting
confidence: 87%
“…These findings resemble the data of nonsinging children described by Siupsinskiene and Lycke [30]. The contrast of frequencies between the sexes is easily visible when comparing 16-year-old males with a minimum frequency of 81.9 Hz (GЬ 2 ) and females with 175.0 Hz (F 3 ), the latter resembling the values found by Lycke and Siupsinskiene [34] for female nonsingers. A similar descent is shown with the variable maximum frequency as depicted above.…”
Section: Discussionsupporting
confidence: 87%
“…However, the following main question remains: which of the methods and voice parameters are the most sensitive to voice training and could better quantitatively describe voice quality, as well as assess voice training effect. According to the literature, to achieve this purpose VRP along with SRP are proposed as relevant methods [4][5][6][10][11][12][13][14][15][16][17][18][19]. Findings of the present study support this opinion.…”
Section: Discussionsupporting
confidence: 78%
“…Several research works have shown that voice training has a quantifiable effect on voice capabilities, mostly on VRP parameters [4,[8][9][10][11][12][13][14][15][16][17][18][19]. Measurements derived from the VRP are useful in identifying voices which are well-equipped; in the diagnosis of vocal dysfunction; in suggesting starting points for voice training and in controlling training effectiveness or outcomes of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Right side: pre-/post-therapeutic comparison via kernel density curves (Gaussian smoothing), in which histograms were shifted and overlaid with smooth density estimates to illustrate the different distributions remediation techniques. Moreover, the influence of singing training on measures of voice quality is also well documented [63,64]. Dastolfo-Hromack et al [65] investigated singing voice outcomes following singing voice therapy in patients with functional and organic dysphonia.…”
Section: Discussionmentioning
confidence: 99%